Model-based cost minimization in noncatalytic biodiesel production plants - Díaz, María Soledad (2009)
In this work, we have formulated a series of nonlinear programming models based on first principles and rigorous thermodynamic predictions, to perform economic evaluation for different scheme alternatives in supercritical methanol transesterification for biodiesel production. The model includes thermodynamic predictions with a group contribution equation of state that have been favorably compared, in this work, to the available experimental data for the different mixtures at different operating conditions. The resulting nonlinear programming problem for cost minimization has been solved with a successive quadratic programming algorithm. Numerical results indicate that the use of a heat pump within the noncatalytic biodiesel production scheme significantly reduces operating costs, making this technology economically competitive as compared to conventional ones.